Pembuatan Minuman Jeli Sari Okra Hijau dan Jambu Biji Merah sebagai Alternatif Selingan Sumber Serat - Emilia Ayu Dimas Widya; Nita Maria Rosiana (Politeknik Negeri Jember, 2020)
Green okra (Abelmoschus esculentus L) and red guava (Psidium guajava L) as the raw materials in jelly drinks is considered as an innovative processing method to increase the fiber content in jelly drinks. This study aims to determine the characteristics and nutritional content of green okra juice jelly drinks (Abelmoschus esculentus L) and red guava (Psidium guajava L) as a distraction source of fiber drinks. The experimental design used was a Completely Randomized Design (CRD)., The formulation for jelly drinks consist of the proportion of which are: P1 (100: 0), P2 (90: 10), P3 (80: 20), P4 (70: 30), P5 (60: 40), P6 (50: 50). Furthermore, the analysis for jelly drinks are fiber content, gel strength and syneresis, organoleptic (hedonic and hedonic quality) and proximate for the best formulation. The results showed that there was a significant increase in fiber levels in each jelly drinks treatment. The more addition of ekstract green okra in the manufacture of jelly drinks, the content of the fiber in jelly drinks was also increasing. The result of the test of fiber on the jelly drinks P1 to P6 respectivelly were 3,45, 3,30, 3,23, 3,12, 3,06, dan 2,95. The result showed were significantly different (P <0.05) on fiber content, gel strength, hedonic quality test on color, aroma, texture and hedonic test on taste, color, and texture. However, there was not significantly different (P> 0.05) on the syneresis test, the hedonic quality test on taste, and the hedonic test on color. The best treatment is jelly drink using 50% green okra ekstract and 50% red guava ekstract. The consume recommendations are 2 portions of jellies per day or 80 grams per day